Provision Of Information Services To Children/Students In Bahbutong Village On Learning Motivation - Abdur Razak; Indah Fitri Ana; Rabiah Nasution; Siti Aisyah Br Purba; Nefi Darmayanti (Jurnal Multidisiplin Sahombu, 2024)
This study aims to describe methods of providing learning motivation to students as a technique to develop their learning abilities and willingness. Learning motivation is crucial elements in the educational process, as it encourages students to actively participate, strive to achieve learning goals, and overcome academic challenges. One logical approach to motivating students is by connecting their learning experiences with their intrinsic motivation, allowing them to feel engaged and purposeful in their educational journey. Information services play a critical role in helping students understand and utilize knowledge to support decision -making processes. Mastery of information is broad benefits, including assisting students in problem- solving, preventing new problems from arising, developing their potential, and maintenance existing capabilities. Through information services, students can gain insights into their surroundings, education, career paths, and socio-cultural aspects, ultimately fostering their abilities to actualize their full potential. This study highlights the importance of providing information services as an effective method to cultivate students ' learning motivation. With appropriate services, students can acquire relevant knowledge to face academic and daily challenges while increasing their awareness of the significance of education.